2017
DOI: 10.1177/1352458517694088
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is associated with a decreased multiple sclerosis risk: The EnvIMS study

Abstract: Our findings suggest that vigorous PA can modify the risk of developing MS independent of established risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 33 publications
4
30
0
3
Order By: Relevance
“…An EnvIMS-based study concluded that vigorous physical activity may decrease the risk of development of MS, but our study found an insignificant association between vigorous physical activity and the development of MS. 32 Another study investigating lifestyle risk factors also found an insignificant association between physical activity and MS. 33 However, a large prospective study using a validated measure of physical activity found weak evidence that higher physical activity may decrease the risk of development of MS. 34 Our study found that a history of measles infection may decrease the risk of MS. Another study found a significant association between measles infection and the development of MS. 35 In a case-control study conducted in 2017 to examine environmental risk factors, a significant association was found between a history of measles or mumps and MS (OR=1.60, 95% CI 1.05-2.45, p =0.029). 36 Another study found that a history of infection during childhood (such as measles) increased the risk of MS. 37 The association between MS and measles infection has been studied for a long time, the association postulated as host response to virus infection because virus may cause demyelinating and inflammatory lesions of MS. 38 …”
Section: Discussionmentioning
confidence: 99%
“…An EnvIMS-based study concluded that vigorous physical activity may decrease the risk of development of MS, but our study found an insignificant association between vigorous physical activity and the development of MS. 32 Another study investigating lifestyle risk factors also found an insignificant association between physical activity and MS. 33 However, a large prospective study using a validated measure of physical activity found weak evidence that higher physical activity may decrease the risk of development of MS. 34 Our study found that a history of measles infection may decrease the risk of MS. Another study found a significant association between measles infection and the development of MS. 35 In a case-control study conducted in 2017 to examine environmental risk factors, a significant association was found between a history of measles or mumps and MS (OR=1.60, 95% CI 1.05-2.45, p =0.029). 36 Another study found that a history of infection during childhood (such as measles) increased the risk of MS. 37 The association between MS and measles infection has been studied for a long time, the association postulated as host response to virus infection because virus may cause demyelinating and inflammatory lesions of MS. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wesnes and colleagues examined the role of vigorous physical activity in the context of the EnvIMS study and reported a similar association as we did after adjusting for the established MS risk factors like sun exposure and smoking. 334 Linking BMI to MS among men strengthens evidence for a role of this factor in MS etiology, as a biological difference by sex seemed little substantiated. However, this study also suggests that BMI is not a valid measure of body fat % among young men, corroborating prior concerns.…”
Section: Interpretation and Contribution Of The Findingsmentioning
confidence: 97%
“…For instance, Tehran and Isfahan with high MS prevalence have urbanizations rates of 85.43 and 92.80, respectively, while Sistan and Balouchestan with an urbanization rate of 49.05 are among the provinces with the lowest MS prevalence. Recent studies indicate that other factors associated with MS risk are also associated with urbanization, such as air pollution, low physical activity, high percentage of smokers, and vitamin D deficiency …”
Section: Discussionmentioning
confidence: 99%